"Selfie-epilepsy": A novel photosensitivity. (April 2017) - Brna, P.M.; Gordon, K.G.
Abstract: Purpose: Photosensitivity is a well-described phenomenon; affecting a relatively small proportion of individuals with epilepsy. Typically people with photosensitive epilepsies are at risk of seizures induced by shimmering natural light, strobe lights and with particular patterns or flicker frequencies on television and video games. Methods & Results: We present a novel case of photosensitivity captured during video EEG monitoring showing reproducible photosensitivity with the ever-popular social phenomenon; the "selfie." The patient had previously demonstrated photosensitive myoclonus with intermittent photic stimulation on routine EEG. Conclusion: This case suggests that taking "selfies" may represent a new area of caution for those with photosensitive epilepsies.